A Flatness-Based Controller for the Stabilization of the Inverted Pendulum. (26th January 2011) - Aguilar-Ibáñez, Carlos; Sira-Ramírez, Hebertt; Suárez-Castañón, Miguel S.
Abstract : We propose a flatness based approach for controlling the inverted pendulum cart system, under the assumption that the pendulum state is always located on a vicinity of its unstable equilibrium point. This is achieved by representing the original system, as a chain of integrators with an additive nonlinear state dependent perturbation. After discarding the small nonlinear perturbation, we may directly use design tools provided by the the flatness approach. The effectiveness and robustness of the obtained control law, which turned out to have a large domain of attraction, were numerically assessed in the context of stabilization and, also, for a reference oscillatory trajectory tracking task.